Association of Sedentary Behavior With Anxiety, Depression, and Suicide Ideation in College Students - Jiang, Liyuan; Cao, Yong; Ni, Shuangfei; Chen, Xiang; Shen, Minxue; Lv, Hongbin; Hu, Jianzhong (Frontiers in Psychiatry, 2020)
Objectives: To investigate the association of sedentary behavior with anxiety, depression, and suicide ideation in multi-centered college students in China. Methods: This was a cross-sectional study of the first-year college student population. The students underwent a questionnaire survey inquiring about sedentary behavior (hours per day) and physical activity (minutes per week) during the past year. Anxiety, depression, and sleep quality were measured by the Generalized Anxiety Disorder Scale (GAD-2), the Patient Health Questionnaire (PHQ-2), and the Pittsburgh Sleep Quality Index (PSQI), respectively. Mixed models were used to estimate the associations, and adjusted odds ratios (AORs) were presented as the effect size. Mediation effect analysis was conducted to test the mediation effect of PSQI. Results: A total of 28298 participants (response rate: 82%) completed the survey and were included in the final analyses. Crude and adjusted estimates consistently showed that both sedentary behavior and physical activity were significantly associated with mental illnesses. Sedentary behavior was positively associated with anxiety, depression, and suicidal behavior in a dose-response manner (AOR: 0.54 to 0.24; ≥ 7h/day as reference), independent from the effect of physical activity (AOR: 0.78 to 0.41; no physical activity as reference). The association of sedentary behavior with mental health was partly mediated by sleep quality (25% to 71%). Conclusions: There is an independent dose-response association of sedentary behavior with mental well-being among college students in China, and this association may be partially attributable to impaired sleep quality. Attention should be drawn and actions should be taken by college educators and mental health providers.